EVALUASI PROGRAM PENCEGAHAN KANKER SERVIK DENGAN METODE INSPEKSI VISUAL ASAM ASETAT (IVA) PADA PASANGAN USIA SUBUR (PUS) DI PUSKESMAS PAGAR JATI - Rismauli Situmorang; Barita Barita; Basyariah Lubis (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Deli Serdang Regency which is one of the Regencies in North Sumatra Province, it is noted that every year the target of early detection of cervical cancer is never achieved. That is, in 2018 to 2019 only 33.59% of the 50% target and in 2020 only 0.4% of the 80% target. One of the working areas of the Puskesmas with low achievement is the Pagar Jati Health Center. In 2019 there were 3,492 women of childbearing age, but only 275 people (7.8%) carried out tests of the target of 15.7%, with a positive IVA of 7 people. This study aims to analyze the evaluation of cervical cancer prevention programs using the Acetic Acid Visual Inspection (IVA) method for couples of childbearing age (PUS) at Pagar Jati Health Center. This study used a qualitative method with a descriptive design. Research subjects were selected using purposive sampling consisting of 5 informants. Data collection techniques using indepth interviews. The results showed that the implementation of the cervical cancer early detection program with the IVA method at the Pagar Jati Health Center had not run optimally. Executors who are still limited are not in accordance with the specified rules. In addition, there is no specific allocation of funds given for program development and there is still a lack of socialization given to the community. Suggestions for related agencies are conducting retraining and increasing the number of trained personnel so that implementation is more optimal and conducting evaluations to increase program achievement.